Differential intensity of rehabilitation silviculture in mismanaged high-graded forest - Vásquez-Grandón, Angélica; Cárcamo, Celso Navarro; Donoso, Pablo J. (Annals of Silvicultural Research, 2023)
There are an estimated two billion hectares of degraded forest worldwide. A high-graded forest is one from which the highest-quality individuals of commercial tree species have been selectively harvested. Successive high-grading results in degradation. Without proper management, these forests are unlikely to recover in the short term and will be unable to fulfil their potential capacity to provide goods and services to society. Human-led rehabilitation is required to restart essential processes such as regeneration. This concept note provides criteria for determining levels of degradation in high-graded old forests, citing implications for rehabilitation silviculture and proposing general strategies for their recovery.